Some sequence spaces on the Orlicz space - haryadi, Haryadi (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami); Vol 1 No 1 (2017): Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai Islami ), 2017)
Although, the Orlicz space is a generalization of classical Banach space , the method used in [4] to construct sequences spaces on  no longer work on the Orlicz space. In this paper, we construct some sequence space in the Orlicz space such that the resulting sequences spaces is a generalization of the sequence space in . We  use modular to construct the Luxemburg norm and describe some topological properties in the spaces.